Business Innovation Strategies for SMEs in Welcoming the New Year: The Perspective of Generation Z as the Main Market - Tusriyanto; Yani, Ahmad; Santosa, Sonny (PT. LITERASI SAINS NUSANTARA, 2024)
This study aims to analyze business innovation strategies for SMEs in welcoming the New Year, with a focus on Generation Z as the primary market. The research employs a qualitative approach using a literature review method, drawing data from scientific articles published between 2010 and 2024 obtained through Google Scholar. Out of 30 articles found, 20 were selected after a rigorous screening process. The analysis shows that Generation Z prefers digital-based innovation, sustainability, personalization, and optimal customer experiences. Case studies of SMEs such as ShopatMaple, TanamKita, and Kopi Kenangan demonstrate that digital marketing strategies, collaborations with influencers, and the reinforcement of sustainability values can enhance SMEs' competitiveness and customer loyalty. This study contributes to understanding how SMEs can leverage the New Year's momentum to create innovations that meet the needs of the Generation Z market.